Tourist clusters, a new approach within the competitive advantages of rural tourism - Espinosa Ortega, Israel Rainiero; Palma, Carolina Guerrero; Iturralde Vallejos, Jaime Alejandro (Tierra Infinita, 2019)
in the 21st century is one of the most important economic sectors worldwide, according to figures it is reflected that it is an economic and global development engine for different sectors; However, the potential of this development generator has been truncated in some initiatives of rural sectors in the northern region of Ecuador, which is why, starting from the competitive advantages mentioned by Michael Porter, it is proposed to implement these advantages so that allow maximize or generate a positive economic impact for the interested sectors, in this case rural tourism ventures, this model will help reduce seasonality, and face the constant updates and trends within a globalized environment. For this reason, it is necessary to break the paradigms, so that we can face the demands of the current market, taking a deeper look at the formation of clusters and production chains intrinsically, within the market landscape of rural tourism involves several companies of the tourism sector and many others that are not, but are linked to the sector. For which it will take companies that are within the same sector and in a certain geographical area, in order to optimize their resources and provide integrated service, contributing to the high segmentation and differentiation of the product. This is intended to show the possibilities offered by networks and the cluster approach for tourism development in rural communities, in addition to creating a space for academic debate, within this approach.